2020
DOI: 10.1177/1938640020933078
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Outcomes and Return to Running After Operative Management of Lisfranc Injuries in a High-Demand Population

Abstract: Background: Literature evaluating outcomes following operative fixation of Lisfranc injuries has demonstrated high rates of chronic disability, particularly in those returning to prior levels of physical function. The purpose of this study is to evaluate the occupational outcomes and return to running after open reduction and internal fixation (ORIF) or arthrodesis for Lisfranc fracture-dislocations in a moderate- to high-demand military cohort. Methods: All active-duty servicemembers undergoing ORIF or primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Symptomatic midfoot arthritis is a common indication for reoperation after fixation of Lisfranc injuries and is known source of patient morbidity. 13 Koehler et al 11 found that 16% of their patients who underwent ORIF with transarticular screws developed arthritis and nearly all required a subsequent arthrodesis procedure. As an alternative to the use of transarticular screws, Alberta et al 2 found that the use of dorsal plating provided a similar reduction as transarticular screws, without the damage to the articular surface.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic midfoot arthritis is a common indication for reoperation after fixation of Lisfranc injuries and is known source of patient morbidity. 13 Koehler et al 11 found that 16% of their patients who underwent ORIF with transarticular screws developed arthritis and nearly all required a subsequent arthrodesis procedure. As an alternative to the use of transarticular screws, Alberta et al 2 found that the use of dorsal plating provided a similar reduction as transarticular screws, without the damage to the articular surface.…”
Section: Discussionmentioning
confidence: 99%